N‐3 Docosapentaenoic Acid Intake and Relationship with Plasma Long‐Chain n‐3 Fatty Acid Concentrations in the United States: NHANES 2003–2014. Issue 4 (26th April 2019) - Richter, Chesney K.; Bisselou, Karl Stessy; Nordgren, Tara M.; Smith, Lynette; Appiah, Adams Kusi; Hein, Nicholas; Anderson‐Berry, Ann; Kris‐Etherton, Penny; Hanson, Corrine; Skulas‐Ray, Ann C.
Abstract: The long‐chain n‐3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), play a crucial role in health, but previous National Health and Nutrition Examination Survey (NHANES) analyses have shown that EPA and DHA intake in the United States is far below recommendations (~250–500 mg/day EPA + DHA). Less is known about docosapentaenoic acid (DPA), the metabolic intermediate of EPA and DHA; however, evidence suggests DPA may be an important contributor to long‐chain n‐3 fatty acid intake and impart unique benefits. We used NHANES 2003–2014 data ( n = 45, 347) to assess DPA intake and plasma concentrations, as well as the relationship between intake and plasma concentrations of EPA, DPA, and DHA. Mean DPA intake was 22.3 ± 0.8 mg/day from 2013 to 2014, and increased significantly over time ( p < 0.001), with the lowest values from 2003 to 2004 (16.2 ± 1.2 mg/day). DPA intake was higher in adults (20–55 years) and seniors (55+ years) compared to younger individuals. In regression analyses, DPA intake was a significant predictor of plasma EPA ( β = 138.5; p < 0.001) and DHA ( β = 318.9; p < 0.001). Plasma DPA was predicted by EPA and DHA intake ( β = 13.15; p = 0.001 and β = 7.4; p = 0.002), but not dietary DPA ( p = 0.3). This indicates that DPA intake is not a good marker of plasma DPA status (or vice versa ), and further research is needed to understand the factors that affect the interconversion of EPA and DPA. These findings have implications for future long‐chain n‐3 fatty acids dietary recommendations.